Brand love and brand forgiveness: An empirical study in Turkey - Merve Yanar Gürce; Petek Tosun; Güzide Öncü Eroğlu Pektaş (Journal of Marketing and Consumer Behaviour in Emerging Markets (JMCBEM), 2022)
Brand love is an interesting and important concept that required further research in brand management. This study tested the impacts of consumer attitudes, subjective norms, and brand anthropomorphization on brand love and brand forgiveness in the framework provided by the theory of planned behavior. Regression analyses showed that brand anthropomorphization and subjective norms have a significant impact on brand love. Brand love positively influences brand forgiveness and acts as a mediator between subjective norms, brand anthropomorphization, and brand forgiveness constructs. Besides mediation, brand anthropomorphization directly influences brand forgiveness. The findings of this study contribute to the existing knowledge on brand love and brand forgiveness concepts by presenting empirical research findings that investigate brand love antecedents. This study has also shown the significant impact of anthropomorphizing a brand on brand forgiveness and brand love.
Keywords: M1; M3; 650; brand love; brand forgiveness; anthropomorphism; retail brands